Between a rock and a hard place: stigma and the desire to have children among people living with HIV in northern Uganda - Barbara Nattabi; Jianghong Li; Sandra C. Thompson; Christopher G. Orach; Jaya Earnest (Journal of the International AIDS Society, 2012)
[BACKGROUND:] HIV-related stigma, among other factors, has been shown to have an impact on the desire to have children among people living with HIV (PLHIV). Our objective was to explore the experiences of HIV-related stigma among PLHIV in post-conflict northern Uganda, a region of high HIV prevalence, high infant and child mortality and low contraception use, and to describe how stigma affected the desires of PLHIV to have children in the future. [METHODS:] Semi-structured interviews were conducted with 26 PLHIV in Gulu district, northern Uganda. The interviews, conducted in Luo, the local language, were audio recorded, transcribed and then translated into English. Thematic data analysis was undertaken using NVivo8 and was underpinned by the "Conceptual Model of HIV/AIDS Stigma" [RESULTS:] HIV-related stigma continues to affect the quality of life of PLHIV in Gulu district, northern Uganda, and also influences PLHIV's desire to have children. PLHIV in northern Uganda continue to experience stigma in various forms, including internal stigma and verbal abuse from community members. While many PLHIV desire to have children and are strongly influenced by several factors including societal and cultural obligations, stigma and discrimination also affect this desire. Several dimensions of stigma, such as types of stigma (received, internal and associated stigma), stigmatizing behaviours (abusing and desertion) and agents of stigmatization (families, communities and health systems), either directly, or indirectly, enhanced or reduced PLHIV's desire to have more children. [CONCLUSION:] The social-cultural context within which PLHIV continue to desire to have children must be better understood by all health professionals who hope to improve the quality of PLHIV's lives. By delineating the stigma process, the paper proposes interventions for reducing stigmatization of PLHIV in northern Uganda in order to improve the quality of life and health outcomes for PLHIV and their children.
Keywords: 330; HIV; stigma; fertility desire; northern Uganda